PROSEDUR JUAL BELI SAHAM YANG GO PUBLIC TETAPI TERHAPUS DARI BURSA EFEK - Auliawati, Nabila; Nugroho, Widhi Cahyo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The progress of the world economy in the field of investment is very much driving changes in life. One of them is investing in stock products on the capital market that can bring profit opportunities, but can also support the country’s economic growth, maintain inflation stability that has occurred this year, not only that, but economic financing to the community has been extended by all levels. Basically, companies that go public that are open to the capital market have high returns, which are also subject to the risks they face. It is important for the government to provide legal certainty that is useful for protecting the interests of society. In investing, there are bankruptcy risks that are unexpected by investors. With the aim of this writing to fulfill the buying and selling procedures when issuers go bankrupt which investors are worried about in bankruptcy in companies that go public in terms of bankruptcy law. With the procedure carried out, it gives investors the right to be given back from the results of the investment made. The result in the bankruptcy of the issuer going public has an impact on the shares owned by investors in a company going public, namely being able to get the risk of loss, namely loss of capital caused by not being able to sell shares of certain investments which affect the delisting process by the stock exchange. There are many cases when a company is removed from stock going public which results in investors losing their investment in the company. In this condition, investors can provide legal protection at this time by taking preventive measures or carrying out judicial matters, namely civil lawsuits can be carried out through assistance from the OJK or by submitting their own submissions to court institutions by investors as shareholders of companies going public